Activities-based Cost Analysis of the Speech Therapy Program at Speech Therapy Unit of Sirindhorn National Medical Rehabilitation Institute - Ruamsuk, Somjit; Thanasriseabwong, Pornpat; Kripanan, Nicha (Journal of The Department of Medical Services, 2024)
Background: About 4-20 percent of acute stroke patients are found to experience communication disorders known as aphasia. Therefore, it is crucial that these patients receive proper assessment and interventions. According to the Speech Therapy Unit of Sirindhorn National Medical Rehabilitation Institute, no study has yet been conducted on the unit cost of speech therapy activities for these patients in Thailand. So, this study aimed to gather data for optimizing resource management and informing policy development. Objectives: The objectives of this study were to conduct a cost analysis and to examine the cost recovery of speech therapy activities for stroke patients with aphasia at the Speech Therapy Unit, Sirindhorn National Medical Rehabilitation Institute. Methods: The research design was descriptive, with data collected retrospectively for the fiscal year 2020. The economic assessment method used was cost analysis from the perspective of the healthcare providers. The term ‘unit cost’ in this study referred to the cost incurred for one speech therapy session for a stroke patient. The cost analysis was conducted using the activity-based costing (ABC) method, and the calculation of cost recovery for both outpatients (OPD) and inpatients (IPD), as well as charge recovery. Results: The cost analysis revealed that the unit cost for individual speech therapy sessions was 305.48 Baht, while the cost for group sessions was 132.99 Baht. However, the service charge for both speech therapy sessions was uniformly set at 300 Baht per session. For OPD patients, the cost recovery was at the rate of 74.54 percent while the charge recovery was at the rate of 98.20 percent. For IPD patients, the cost recovery was at the rate of 74.31 percent while the charge recovery was at the rate of 98.20 percent. Overall, the cost recovery rate for patients receiving the service was 74.47%, while the charge recovery rate was 98.20%. Conclusion: Given that labor costs are the highest but the service charge falls short of covering these costs, this indicates a loss for individual speech therapy sessions. However, group speech therapy sessions continue to generate profits. Therefore, to achieve cost recovery, it is recommended that the service charge for individual speech therapy sessions be increased to match the actual unit cost. Additionally, greater emphasis should be placed on promoting group speech therapy sessions. It is also important to consider each patient's condition and select the most appropriate therapy to ensure safety and effectiveness in treatment.